Impact of sensor-based wastewater irrigation scheduling on physical and microbiological health of soil in chrysanthemum (Chrysanthemum Morifolium Ramat.) - Ankit; D.S. Gurjar; K.G. Rosin; Kapila Shekhawat; Ritu Jain (Annals of Agricultural Research, 2023)
A field trial was undertaken to study the impact of sensor-based wastewater irrigation scheduling on physical and microbiological health of soil in chrysanthemum (Chrysanthemum Morifolium Ramat.) at Water Technology Centre (WTC), ICAR-Indian Agricultural Research Institute (IARI), New Delhi 110012 throughout the year 2019-20. Study was conducted with following six treatments namely, T1 : Scheduling irrigation with groundwater at 25% Maximum Allowable Depletion (MAD), T2 : Scheduling irrigation with groundwater at 50% MAD, T3 : Scheduling irrigation with groundwater at 75% MAD, T4 : Scheduling irrigation with wastewater at 25% MAD, T5 : Scheduling irrigation with wastewater at 50% MAD, T6 : Scheduling irrigation with wastewater at 75% MAD and was established in a Randomized Block Design (RBD) in open field condition with four replication. Results shows that physical properties of soil such as bulk density, water retention at field capacity, water retention at permanent wilting point, porosity and saturated hydraulic conductivity were not significantly changed with varied groundwater and wastewater irrigation scheduling regimes at different MAD values. However, population density of both fecal coliform and total coliform bacteria was found significantly higher when wastewater irrigation applied at 75 % MAD (T6 ) compared to other irrigation regimes.